Ipsilateral fractures of the femoral neck, shaft and distal end: long-term outcome of five cases - Douša, Pavel (Springer-Verlag, 2010)
Out of 52 cases of ipsilateral femoral fractures treated at a level I trauma centre between June 1994 and March 2008, the diaphyseal fracture was accompanied by a intracapsular neck fracture in only 20 cases. In the rest of the cases, the diaphyseal fracture was combined with either an extracapsular or pertrochanteric fracture. Five of these patients also had fractures of the distal femur. In three of those patients we began treatment with osteosynthesis of the femoral neck and shaft, using a reconstruction nail, then stabilized the distal fracture with a 95° blade plate or with lag screws. In the other two cases, initial treatment dealt with the distal femoral fracture, stabilizing it with a 95° blade plate, which was also used for stabilization of the diaphyseal fracture. In these patients, the proximal fracture was treated using dynamic hip screws (DHS). All fractures healed, two after initial treatment, while the other three needed one reoperation. The follow-up period was 2–13 years after the injury. The order in which fractures are treated is best left to the discretion of the physician and the circumstances. In our experience, two implants are sufficient for osteosynthesis, one for stabilizing one end of the femur together with the shaft, and the other is used for treating the other end of the femur.